Modulation of the mechanism of apoptosis in cancer cell lines by treatment with silica-based nanostructured materials functionalized with different metallodrugs. Issue 35 (16th August 2018) - Díaz-García, Diana; Cenariu, Diana; Pérez, Yolanda; Cruz, Paula; del Hierro, Isabel; Prashar, Sanjiv; Fischer-Fodor, Eva; Gómez-Ruiz, Santiago
Abstract : The mechanism of apoptosis triggered by organotin- or titanocene-modified SBA-15 materials has been studied. Abstract : The mesoporous silica-based material SBA-15 (Santa Barbara Amorphous-15) has been modified with the aminodiol ligand 3-[bis(2-hydroxyethyl)amino]propyltriethoxysilane (PADOH) to give the corresponding material SBA-PADOH. Subsequent functionalization with a diorganotin(iv ) compound, SnPh2 Cl2 (1 ), and with two titanocene derivatives, TiCp2 Cl2 ([Ti(η 5 -C5 H5 )2 Cl2 ] (2 )) and TiCpCp PhNf Cl2 ([Ti(η 5 -C5 H5 )(η 5 -C5 H4 CHPhNf)Cl2 ] (3 ) (Ph = C6 H5 ; Nf = C10 H7 )), gave the materials SBA-PADO-SnPh2 (M1 ), SBA-PADO-TiCp2 (M2 ) and SBA-PADO-TiCpCp* (M3 ), respectively. SBA-PADOH andM1–M3 have been characterized by various techniques such as FT-IR, XRD, XRF, solid-state NMR, nitrogen adsorption–desorption isotherms, electrochemical methods, SEM and TEM, observing that the functionalization has mainly taken place inside the pores of the corresponding porous system. In addition, mechanistic aspects of the apoptosis triggered by the synthesized materials have been studied in vitro in tumour cell lines derived from three distinct types of cancer in order to elucidate their growth inhibition and interference with the expression of tumour necrosis factor alfa (TNF-α) and the first apoptosis signal receptor (Fas or tumour necrosis factor receptor 6). It was observed that the antiproliferative and proapoptotic capacity of the materials depends on their functionalization with the different cytotoxic prodrugs (organotin or titanocene derivatives). The study shows thatM1–M3 influence the metabolic activity of the tumour cells and modulate the apoptotic pathways by different mechanisms, according to the active compound inside the material.